IT für soziale Inklusion Digitalisierung - Künstliche Intelligenz - Zukunft für alle - Burchardt, Aljoscha; Uszkoreit, Hans (De Gruyter, 2018)
Social Inclusion is a topic of growing importance in all walks of life. Their enforcement is often not possible without information technology. The book describes the state of research. However, the focus is on tools and applications from the areas of education, health, mobility, migration and others. Topics and authors come from the workshop of the same name, which the DFKI designed as part of the VISION SUMMIT 2016.